2017
DOI: 10.1111/jmft.12259
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Supervision Evaluation: An Actor–Partner Relational Model

Abstract: This article contributes to research practices in marital and family therapy, specifically the dyadic and development over time in clinical supervision, and describes and applies methodological strategies to develop measurements congruent with the systemic and developmental principles of the field. This project evaluates the psychometric properties of the dyadic supervision evaluation (DSE) in terms of measurement equivalence and causality. A structural equation analysis is conducted utilizing the actor-partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Many council members expressed appreciation for the quality of writing and the depth of scholarship on this manuscript. One indicated that, “their literature review is concise yet exhaustive; the writing is great, methodology solid, and I think it synthesizes many facets of couple therapy .” Finally, Dyadic Supervision Evaluation: An Actor‐Partner Relational Model by authors Adrian Avila, Brian Distelberg, Ana Estrada, Lauren Foster, Mary Moline, and Douglas Huenergardt () also received an honorable mention. In the words of one council member, this article represents a “ significant contributor to moving the field forward as it provides some quantifiable legitimacy to supervision.…”
Section: Article and Reviewers Of The Yearmentioning
confidence: 99%
“…Many council members expressed appreciation for the quality of writing and the depth of scholarship on this manuscript. One indicated that, “their literature review is concise yet exhaustive; the writing is great, methodology solid, and I think it synthesizes many facets of couple therapy .” Finally, Dyadic Supervision Evaluation: An Actor‐Partner Relational Model by authors Adrian Avila, Brian Distelberg, Ana Estrada, Lauren Foster, Mary Moline, and Douglas Huenergardt () also received an honorable mention. In the words of one council member, this article represents a “ significant contributor to moving the field forward as it provides some quantifiable legitimacy to supervision.…”
Section: Article and Reviewers Of The Yearmentioning
confidence: 99%
“…Further, attachment anxiety and avoidance have also shown to have a significant impact upon MFT supervision and training and should be considered in the use of telehealth supervision (Marmarosh et al, 2013; McKibben & Webber, 2017). The supervisory relationship serves as the foundation on which trainees gain clinical skills, such as treatment planning, therapeutic intervention, and professional conduct (Avila et al, 2018; Morgan & Sprenkle, 2007). It is also important to consider specific supervision tasks (e.g., delivery of performance feedback), which have shown to be a critical component of the supervisory relationship (Turner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%